Melayu dan Sriwijaya: Tinjauan Tentang Hubungan Kerajaan–kerajaan di Sumatera pada Zaman Kuno - Arif Rahim (Universitas Batanghari Jambi, 2019)
This paper discusses the issue of the relationship of the Melayu kingdom with other kingdoms on the island of Sumatra in ancient times, especially with the Srivijaya kingdom. This prob this paper discusses the issue of the relationship between the Malay kingdom and other kingdoms on the island of Sumatra in ancient times, especially with the Srivijaya kingdom. This issue is considered important because until now there are still many issues that provoke debate, especially regarding the existence of the two kingdoms when related to the interpretation of historical sources. The results of this study are expected to contribute to the development of knowledge, especially about the local history of Jambi, and can be used as material for consideration by relevant institutions in order to preserve historical and cultural values and for the development of the Jambi tourism industry. By using a multidimensional approach and supported by the application of historical methods that refer to scientific historical research procedures, it is hoped that the questions raised in the formulation of the problem will be objectively and systematically expressed. From this research, it is known that before the information about the Kingdom of Malay and Srivijaya in the 7th century, four centuries earlier on the island of Sumatra, a number of kingdoms had developed relations with the outside world, especially China and India. The kingdoms are Koying, Tupo, Tulangbawang, and Kantoli. No clear connection is known about the relationship between these four kingdoms with the Malay Kingdom which emerged later. Experts try to conclude that the Tupo Kingdom is the port of Koying. The emergence of the 5th century Kantoli Kingdom led to the end of Koying and Tupo, and subsequently the existence of Kontoli was replaced by the Malay Kingdom. The latter did not last long as an independent kingdom, because it was defeated by Srivijaya in 683. Until the 11th century Malay was part of Srivijaya. However, Malay continued to develop as an important port within Srivijaya's power. Srivijaya suffered a setback after a series of Cola Kingdom attacks from South India. This opportunity was used by Malay to break away, until it emerged as the most important kingdom in Sumatra in the 14th century.